2007
DOI: 10.1093/rpd/ncm245
|View full text |Cite
|
Sign up to set email alerts
|

Exposure caused by wireless technologies used for short-range indoor communication in homes and offices

Abstract: In order to estimate typical radio frequency exposures from indoor used wireless communication technologies applied in homes and offices, WLAN, Bluetooth and Digital Enhanced Cordless Telecommunications systems, as well as baby surveillance devices and wireless headphones for indoor usage, have been investigated by measurements and numerical computations. Based on optimised measurement methods, field distributions and resulting exposure were assessed on selected products and real exposure scenarios. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Reducing the highest allowed level of RF EMR, and the establishment of other legislation on High Frequency Electromagnetic Dosimetry, are issues of worldwide importance, taking into consideration the contradictory information about mobile phones, mobile telephony base stations, and their possible dangerous effects on human health [17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Reducing the highest allowed level of RF EMR, and the establishment of other legislation on High Frequency Electromagnetic Dosimetry, are issues of worldwide importance, taking into consideration the contradictory information about mobile phones, mobile telephony base stations, and their possible dangerous effects on human health [17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…The modulation schemes employed by 802.11b WLANs include spread spectrum, whereas the later a and g variants use OFDM. The access is TDD, using a carrier sense multiple access with collision avoidance (CSMA/CA), which means that the timing structure may be more random and dependent on the general interference from other users [IEEE Standard, 2007;Schmid et al, 2007]. An example of the power fluctuations near a laptop while uploading files is illustrated in Figure 5 a,b.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to baby monitors has rarely been investigated: Schmid et al [] and Kühn et al [] investigated exposure to baby monitors within larger studies on exposure to short‐range indoor wireless communication devices. We investigated the exposure, in terms of both the peak spatial‐averaged specific absorption rate (SAR) in 10 g of tissue and the time‐averaged root‐mean‐squared (RMS) electric (E) field, induced by baby monitors operating in a frequency range between 400 MHz and 2.45 GHz.…”
Section: Overview Of the Selected Baby Monitors Their Communication mentioning
confidence: 99%
“…Under the assumption of a continuous transmitted burst, the marmitek babyview 725 yielded the maximum RMS electric field of 5 V/m, which is about a factor 12 below the ICNIRP reference level. Schmid et al [2007] reported electric fields ranging from 0.4 till 1.1 V/m, which are in line with the values observed in our study. K€ uhn et al [2007] observed larger electric fields (3.2 V/m), which might originate from a 40 MHz device.…”
mentioning
confidence: 99%